Sobre eróticas fantasmagorías y obscenos andares: desvíos parisinos en la prosa de Augusto d'Halmar (Revista de Crítica Literaria Latinoamericana, 2023)
Through a queer reading of the nouvelle “Dariel o el alma en pena de la muchedumbre” (1935), by the Chilean author Augusto D’Halmar, this essay studies the deviant rhetoric with which this queer author literally imagines Paris. As a hypothesis, I postulate that, by means of a cinematographic rhetoric, the story ghostly stages the homoerotic nocturnal walks of Lieutenant Cristián Davis through the City of Lights, arguing with those straight modern imaginaries erected, during the Latin American fin de siècle, by three famous members of the lettered city: José Martí, Rubén Darío and Horacio Quiroga.
Keywords: Queer studies; Latin American fin de siècle; Paris; cinema; cruising; gigolo